Analisis Dan Perancangan Sistem Informasi Manajemen Aset Berbasis Web Menggunakan Standar ISO/IEC 25010 - Diharphyta Ningrum Hadijoyo; Remo Teguh Yudianto; Chairul Anwar (PT Jurnal Cendekia Indonesia, 2026)
Asset management conducted manually frequently leads to challenges, including mistakes in documentation, redundant data, slow information distribution, and complications in asset tracking. These issues highlight the necessity for an information system that can handle asset information in a more unified, quicker, and precise way. This research aims to examine and construct a web-based asset management system utilizing the Prototype method and system modeling with the Unified Modeling Language (UML). The Prototype method was selected because it allows for progressive development of the system through initial design creation, user evaluation, and ongoing enhancements based on evolving requirements. The phases of the research involve determining user requirements, designing the system with UML, developing a prototype, testing, and assessing software quality as per the ISO/IEC 25010 standard. This standard evaluates the quality attributes of the system, which include functional suitability, usability, reliability, performance efficiency, security, compatibility, maintainability, and portability. The results of the research show that the proposed system can improve the efficiency of asset management through enhanced data recording, searching, categorization, and reporting capabilities. As a result, this system is anticipated to contribute significantly to asset management in organizations or companies.